China–U.S. Trade Friction and China’s Agricultural Machinery Imports: Mechanism and Empirical Evidence - Xinyi Li; Meng Zhang (Agriculture)
Based on the monthly panel data of China’s imports of agricultural machinery products from 2016–2022, this paper uses a multi-period double-difference model to assess the impact of China’s imposition of counter-tariffs on China’s imports of agricultural machinery in the context of U.S.–China trade friction. It is found that China’s implementation of counter-tariffs significantly reduces China’s imports of agricultural machinery products from the U.S. and significantly increases imports from 16 other countries, but the trade diversion effect is lower than the trade suppression effect. Mechanism analysis finds that China–U.S. trade friction affects the technological innovation capacity of agricultural machinery enterprises and the degree of uncertainty in the Chinese economy, which in turn affects China’s agricultural machinery imports. Heterogeneity analysis finds that China–U.S. trade friction has a more significant inhibitory effect on seeding and planting and fertilizing machinery, drainage, irrigation, and water lifting machinery, and other machinery imported from the U.S., and a more significant diversionary effect on agricultural primary processing machinery and harvesting machinery imported from 16 other countries. The imposition of countervailing tariffs mainly affected imports of complete machinery products rather than machinery spare parts.